2006
DOI: 10.1089/ars.2006.8.1987
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Encephalomyelitis Induces Changes in DJ-1: Implications for Oxidative Stress in Multiple Sclerosis

Abstract: DJ-1 plays an important role in oxidative stress, and is involved in various neurodegenerative diseases. Accumulating evidence suggests a central role for oxidative stress in multiple sclerosis (MS). The aim of this study was to examine whether changes occur in DJ-1 expression in an animal model of MS, experimental autoimmune encephalomyelitis (EAE). We found upregulation of DJ-1 mRNA and protein expression levels in EAE and a correlation between disease severity and increased DJ-1 levels. Although DJ-1 isofor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…This result is very much like that of the activation of oxidative stress referred for the EAE model by Lev et al, [42] and a similar performance has been reported for MS patients, where an up-regulation of lipid peroxidation has been found [43]. The lowering of this process by C-Pc may be exploited, encouraging this therapeutic approach, since lipid oxidation induces structural and functional cell failure.…”
Section: Discussionsupporting
confidence: 84%
“…This result is very much like that of the activation of oxidative stress referred for the EAE model by Lev et al, [42] and a similar performance has been reported for MS patients, where an up-regulation of lipid peroxidation has been found [43]. The lowering of this process by C-Pc may be exploited, encouraging this therapeutic approach, since lipid oxidation induces structural and functional cell failure.…”
Section: Discussionsupporting
confidence: 84%
“…Sensitivity of motor neurons to reactive nitrogen species has implications for MS [125]. Additional evidence suggests a central role for OS in MS [126]. MS patients display elevated TBARS levels, reduced protein SH groups and slightly reduced SOD [127].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…In the current study, we analyze the functional implication of the disease vs. control homozygote haplotypes in three neuronal cell lines LAN-5, U-87 MG, and N2A. These three cell lines have been widely used for the analysis of gene expression in neurodegenerative disorders (Businaro et al, 2006;Lev et al, 2006;Mandel et al, 2008;Qing et al, 2008).…”
Section: Discussionmentioning
confidence: 99%